Distributed model for changes in river peak flow due to land development - Y. M., Mustafa; Mohd Amin, Mohd Soom, Prof. Ir. Dr.; Lee, Teang Shui, Prof. Ir. Dr.; Abdul Rashid, Mohamed Shariff, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/